Risk and return in Asian emerging markets : a practitioner's guide - Cakici, Nusret; Topyan, Kudret; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Risk and Return in Asian Emerging Markets offers readers a firm insight into the risk and return characteristics of leading Asian emerging market participants by comparing and contrasting behavioral model variables with predictive forecasting methods.
Keywords: Accounting; Bookkeeping; Business enterprises -- Finance; Finance; Risk management; Econometrics; Development economics